The effect of simvastatin treatment on bone repair of femoral fracture in animal model - Mardegan Issa, João Paulo; Lucia, Conrado Ingraci de; Santos Kotake, Bruna Gabriela dos; Gonzaga, Miliane Goncalves; Tocchini de Figueiredo, Fellipe Augusto; Iyomasa, Daniela Mizusaki; Macedo, Ana Paula; Ervolino, Edilson [UNESP] (Informa Healthcare, 2015)
The aim of this research was to evaluate the fracture healing area in osteoporotic femur of female rats restrained by stainless steel wire by statin administration in two different doses (5 mg and 20 mg). Ninety female rats were divided into six groups (n = 15): SH, SH-5 mg, SH-20 mg, OVX, OVX-5 mg, and OVX-20 mg. The surgery consisted of the fracture of the left femur bone and stabilization by K-wire and the administration was restricted and weekly controlled in the drinking water. The euthanasia was conducted at three different moments, five animals per period: 7 d, 14 d, and 28 d. Densitometry, zymography, and histological analyses showed a significant difference between some groups. According to these findings, simvastatin promoted a positive action for bone repair, especially in the osteometabolic group treated with 20 mg of the drug.
Keywords: Fracture healing; MMP and ovariectomy; Statins; Simvastatin